Available Micronutrient Status of Soils Degraded Due to Irrigation with Residual Sodium Carbonate/Saline Water - Joshi, D C (Annals of Arid Zone, 2016)
Soils irrigated with saline water were adequate in iron, manganese and copper but marginal in zinc. Amongst soils irrigated with high residual sodium carbonate water zinc and manganese were deficient respectively in 50 and 5 percent samples while copper was marginal in 15 percent samples. Regression of salinity parameters on the available micronutrients has been discussed.